Simulasi Topologi Dan Pengalamatan Jaringan LAN Pada Gedung Teknik Elektro Universita XYZ - Antuanet, Nerisa Beatrix; Aryanta, Dwi (e-Proceeding FTI, 2024)
Network topology is a design that shows how the arrangement or location of computers with one another, The topology used in research is tree topology and star topology, in addition to functioning to show the arrangement of topology computer Nodes as monitoring to evaluate and see Network paths. On a computer Network there is a class of Addresses or commonly called an IP Address class which functions to assign a name or number to each computer connected to the Network. In maximizing computer Networks in electrical buildings, a simulation design is carried out using Cisco Packet Tracer software to facilitate and maximize building computer Networks. The results of this study every device connected to the Network will get an IP Address automatically called Dynamic Host Configuration Protocol (DHCP) which is set on the server. Server as a maintainer in a Network. Keywords: Network Topology, IP Address, Cisco Packet Tracer, DHCP, Server. Network topology is a design that shows how the arrangement or location of computers with one another, The topology used in research is tree topology and star topology, in addition to functioning to show the arrangement of topology computer Nodes as monitoring to evaluate and see Network paths. On a computer Network there is a class of Addresses or commonly called an IP Address class which functions to assign a name or number to each computer connected to the Network. In maximizing computer Networks in electrical buildings, a simulation design is carried out using Cisco Packet Tracer software to facilitate and maximize building computer Networks. The results of this study every device connected to the Network will get an IP Address automatically called Dynamic Host Configuration Protocol (DHCP) which is set on the server. Server as a maintainer in a Network. Keywords: Network Topology, IP Address, Cisco Packet Tracer, DHCP, Server. ABSTRAK Topologi jaringan merupakan sebuah desain yang menunjukan cara penataan atau letak komputer satu dengan yang lainnya, topologi yang digunakan dalam penelitian yaitu topologi pohon dan bintang, selain berfungsi untuk menunjukan penataan Node komputer, topologi sebagai monitoring untuk mengevaluasi dan melihat jalur jaringan. Pada jaringan komputer terdapat pengkelasan alamat atau biasa disebut IP Address class yang dimana berfungsi memberikan untuk nama atau nomor ke setiap komputer yang terhubung pada jaringan. Dalam memaksimalkan jaringan komputer pada gedung elektro maka dilakukanlah perancangan simulasi menggunakan software Cisco Packet Tracer untuk memudahkan dan memaksimalkan membangun jaringan komputer. Hasil dari penelitian ini setiap perangkat yang terhubung pada jaringan maka akan mendapatkan IP Address secara otomatis biasa disebut Dynamic Host Configuration Protocol (DHCP) yang diatur pada bagian server. Server sebagai pengelola dalam sebuah jaringan. Kata kunci: Cisco Packet Tracer, DHCP, IP Address Server, Topologi Jaringan.